Occurrence, sources and transport of antibiotics in the surface water of coral reef regions in the South China Sea: Potential risk to coral growth. (January 2018) - Zhang, Ruijie; Zhang, Ruiling; Yu, Kefu; Wang, Yinghui; Huang, Xueyong; Pei, Jiying; Wei, Chaoshuai; Pan, Ziliang; Qin, Zhenjun; Zhang, Gan
Abstract: Laboratory research has indicated that antibiotics had negative effects on coral growth by disturbing natural microbiota; however, no field studies have reported antibiotic contamination levels and their influence on coral growth in natural coral reef regions (CRRs). This study investigated antibiotic occurrence and sources in the surface water from CRRs that have suffered from rapid coral degradation and evaluated their risk to coral growth. These regions are in the South China Sea, including four coastal and two offshore CRRs. The results show that 13 antibiotics were detected in the coastal CRRs with concentrations ranging from 10 −2 –10 0  ng L −1, while 5 antibiotics occurred in offshore CRRs (300–950 km from the mainland), with concentrations ranging from 10 −2 to 10 −1  ng L −1 . Their concentrations decreased gradually from the coast to offshore in the transport process. However, Yongxing Island, which is approximately 300 km from the mainland, was an exception with relatively higher concentrations than the surrounding reefs because of the ever-increasing human activity on the island. The presence of anthropogenic contaminants antibiotics in CRRs may be a potential risk to coral growth. Graphical abstract: Highlights: The study first studied antibiotic contamination in seawater from coral reef regions. Thirteen antibiotics were detected at the level of 10 −2 - 10 0  ng L −1 . The antibiotic concentrations decreased gradually from the coast to offshore. Higher concentrations were detected in one offshore reef with more human activities. Potential risk of the antibiotics to the coral could be ruled out. Abstract : Antibiotic contamination level, sources and their potential risk to coral growth were first studied in the surface water of natural coral reef regions.